Foreclosure externalities: Some new evidence - Kristopher Gerardi; Eric Rosenblatt; Paul S. Willen; Vincent W. Yao (Federal Reserve Bank of Atlanta, 2012)
In a recent set of influential papers, researchers have argued that residential mortgage foreclosures reduce the sale prices of nearby properties. We revisit this issue using a more robust identification strategy combined with new data that contain information on the location of properties secured by seriously delinquent mortgages and information on the condition of foreclosed properties. We find that while properties in virtually all stages of distress have statistically significant, negative effects on nearby home values, the magnitudes are economically small, peak before the distressed properties complete the foreclosure process, and go to zero about a year after the bank sells the property to a new homeowner. The estimates are very sensitive to the condition of the distressed property, with a positive correlation existing between house price growth and foreclosed properties identified as being in above average condition. We argue that the most plausible explanation for these results is an externality resulting from reduced investment by owners of distressed property. Our analysis shows that policies that slow the transition from delinquency to foreclosure likely exacerbate the negative effect of mortgage distress on house prices.
Keywords: G21; K11; R31; 330; foreclosure; mortgage; judicial; power of sale; right to cure; Hypothek; Notleidende Kredite; Immobilienpreis; Nachbarschaft; Schätzung; USA